Lawyers Making Meaning - Broekman, Jan M. author. aut Link
XIV, 258 p.
Keywords: This book present a structure for understanding and exploring the semiotic character of law and law systems. Cultivating a deep understanding for the ways in which lawyers make meaning—the way in which they help make the world and are made, in turn by the world they create —can provide a basis for consciously engaging in the work of the law and in the production of meaning. The book first introduces the reader to the idea of semiotics in general and legal semiotics in particular, as well as to the major actors and shapers of the field, and to the heart of the matter: signs. The second part studies the development of the strains of thinking that together now define semiotics, with attention being paid to the pragmatics, psychology and language of legal semiotics. A third part examines the link between legal theory and semiotics, the practice of law, the critical legal studies movement in the USA, the semiotics of politics and structuralism. The last part of the book ties the different strands of legal semiotics together, and closely looks at semiotics in the lawyer’s toolkit—such as: text, name and meaning.